Pengaruh Bantuan Kemanusiaan Indonesia pada Gempa Turki 2023 Terhadap Hubungan Kedua Negara - Minasari, Arofah; Murakabhi, Estafetta Chrysantina; Devangga Idham, Rayhan; Datu Wiryawan, Rian (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2024)
This research aims to analyze the impact of Indonesia's post-earthquake humanitarian assistance in Türkiye on the dynamics of relations between the two countries. Aid activities have an impact on the political, social and economic conditions of bilateral relations between Indonesia and Türkiye. The results of this research show that Indonesia's humanitarian assistance during the Türkiye Earthquake had a positive impact on bilateral relations. Politically, Indonesia is able to improve Indonesia's good image as a country that has a high sense of concern. Socially, it is able to deepen emotional feelings and strengthen the sense of solidarity between communities in the two countries. Meanwhile, economically, Indonesia is able to open up opportunities for economic cooperation and build trust in trade and investment relations. So it can be concluded that this assistance strengthens positive relations between Indonesia and Türkiye in creating a solid foundation for future cooperation